A review of liver dysfunction in the lung transplant patient. Issue 8 (25th May 2021) - Hyzny, Eric J.; Chan, Ernest G.; Morrell, Matthew; Harano, Takashi; Sanchez, Pablo G.
Abstract: Liver dysfunction is an increasingly common finding in patients evaluated for lung transplantation. New or worsening dysfunction in the perioperative period, defined by presence of clinical ascites/encephalopathy, high model for end‐stage liver disease (MELD) score, and/or independent diagnostic criteria, is associated with high short‐ and long‐term mortality. Therefore, a thorough liver function assessment is necessary prior to listing for lung transplant. Unfortunately, identification and intraoperative monitoring remain the only options for prevention of disease progression with isolated lung transplantation. Combined lung and liver transplantation may provide an option for definitive long‐term management in selecting patients with known liver disease at high risk for postoperative progression. However, experience with the combined operation is extremely limited and indications for combined lung and liver transplant remain unclear. Herein, we present a comprehensive literature review of patients with liver dysfunction undergoing lung transplantation with and without concurrent liver transplant in an effort to illuminate the risks, benefits, and clinical judgement surrounding decision to pursue combined lung‐liver transplantation (CLLT). We also argue description of liver function is currently a weakness of the current lung allocation scoring system. Additional algorithms incorporating liver function may aid in risk stratification and decision to pursue combined transplantation.